华文课本的落地生根：马来西亚华文独立中学课本中的“马来西亚华人”身份建构 = The rooting of Chinese textbooks: a study of “Malaysian Chinese” identity construct in Malaysian Chinese independent high school textbooks - 陈柏霖 Tan, Pek Lim (Nanyang Technological University, 2023)
本文为了更清晰认识独中教育所传承文化之“根”，对独中课本中最重要的华文课本建构之“马来西亚华人”概念予以关注。本文以董总2004年版和2019年版初中《华文》为研究对象，拟从中发掘独中华文课本的编撰意识、版本差异以及独中教育对 “马来西亚华人” 概念的建构。2019年版《华文》遵循1951年《方吴报告书》对马来亚华校教科书提出融合民族文化与国家意识的改编方向，并纳入了马来西亚文化元素。此外，2019年版《华文》具现代化跨学科的教学模式，体现以学生为教学主体的教育精神。在课文收录方面强调本土意识，体现华语语系意识，同时打破传统文言文体裁式教学，融合文言文与马华文学，创制独特的马华文学的美学意识。独中教育透过2019年版《华文》具体构建出包含坚持母语教育、以马来西亚为家乡和效忠对象、融合民族文化和马来西亚文化的 “马来西亚华人” 建构，使2019年版《华文》成为较2004年版更具有教科书改编历史意义，见证马来西亚华人文化 “落地生根” 的现代独中教科书。This article seeks to understand the “root” of the cultural inheritance of Malaysian Chinese Independent High Schools, to which attentions were given to a "Malaysian Chinese" concept constructed by the Chinese textbooks that are taught in the most important subject in the system. Taking DongZong's 2004 edition and 2019 edition of Junior level Chinese textbooks as the research subject, this article explores the compilation consciousness, the version differences, and the "Malaysian Chinese" concept constructed by Malaysian Chinese Independent High School Education System in the Chinese textbooks. The 2019 edition Chinese textbooks adopted 1951 "Chinese Education Report" suggestions for Malayan Chinese School textbooks, other than integrating ethnic culture and nationalism, elements of Malaysian culture were incorporated. In addition, the 2019 edition Chinese textbooks also adopted modern interdisciplinary teaching model, which embodies the educational spirit of students as active learners. The texts included emphasises and reflects on local and Sinophone study consciousness, at the same time consciousness on unique Malaysian Chinese literature aesthetic was formed through the teaching of classical literature. The 2019 edition Chinese textbook constructed the "Malaysian Chinese" concept that includes the protection of mother tongue education, Malaysia as their hometown and allegiance, and the integration of ethnic culture and Malaysian culture. Comparing to 2004 edition, the 2019 edition Chinese textbooks is significant in the Chinese textbook adaptation history that witnessed the "rooting" of the local Malaysian Chinese culture.